Preparation of Ag/Au/Pt nanoparticles and their catalytic properties - Ongartkit A. (Elsevier, 2014)
The Pt deposited on hollow Ag/Au nanoparticles (Ag/Au/Pt) was successfully prepared by a successive reduction method. In general, no absorption peak at UV-visible region similar to that of Pt nanoparticles was observed for these Ag/Au/Pt nanoparticles. Almost spherical nanoparticles with average size around 20 nm were revealed by TEM. The presence of constituent metal of Ag/Au/Pt was confirmed by EDS. The catalytic properties of Ag/Au/Pt for methanol oxidation were investigated by cyclic voltammetry. The peak current density of the Ag/Au/Pt nanoparticles is higher than that of Pt nanoparticles, indicating their better potential of an electrocatalytic activity for methanol oxidation. © 2014 Elsevier B.V. All rights reserved.